Elevated gamma-rays shielding property in lead-free bismuth tungstate by nanofabricating structures. (January 2018) - Liu, Jun-Hua; Zhang, Quan-Ping; Sun, Nan; Zhao, Yang; Shi, Rui; Zhou, Yuan-Lin; Zheng, Jian
Abstract: Radiation shielding materials have attracted much attention across academia and industry because of the increasing of nuclear activities. To achieve the materials with low toxicity but good protective capability is one of the most significant goals for personal protective articles. Here, bismuth tungstate nanostructures are controllably fabricated by a versatile hydrothermal treatment under various temperatures. The crystals structure and morphology of products are detailedly characterized with X-ray diffraction, electron microscope and specific surface area. It is noteworthy that desired Bi2 WO6 nanosheets treated with 190 °C show the higher specific surface area (19.5 m 2 g −1 ) than that of the other two products. Importantly, it has a close attenuating property to lead based counterpart for low energy gamma-rays. Due to the less toxicity, Bi2 WO6 nanosheets are more suitable than lead based materials to fabricate personal protective articles for shielding low energy radiations and have great application prospect as well as market potential. Graphical abstract: Highlights: Desired Bi2 WO6 nanosheets are obtained. Surface effects of nanostructures promote the attenuation of low energy gamma-rays. Nanostructures have the potential to replace lead based materials for personal protective articles.